eGFR partially mediates the association between Dietary Inflammatory Index and all-cause mortality in older adults - Tingting Hu; Ying Zhang; Zhu Chen; Zhifen Zhang; Jun Su (Medicine, 2026)
This study examines the association between the Dietary Inflammatory Index (DII) and all-cause mortality in older adults and investigates the mediating role of estimated glomerular filtration rate (eGFR) using National Health and Nutrition Examination Survey data. We included 6300 participants aged ≥ 60 years from 9 National Health and Nutrition Examination Survey cycles (2001–2018). All-cause mortality (ascertained via linkage to the National Center for Health Statistics) was the primary endpoint. Cox proportional hazards models evaluated the association. Mediation analysis (mediation package, R 4.4.0) quantified eGFR’s contribution. The average DII of the enrolled subjects was 0.73 (0.04), and the average age was 68.84 (0.13) years. Over 116.4 months of follow-up, 1746 all-cause deaths occurred. Each 1-unit DII increase increased all-cause mortality risk by 5.6% (adjusted hazard ratio = 1.056, 95% confidence interval [CI]:1.020–1.094; P = .002). The highest DII tertile had 26% higher all-cause mortality vs the lowest (hazard ratio = 1.26, 95% CI:1.08–1.48). eGFR mediated 9.67% (95% CI:3.65–25.7%) of the DII-all-cause mortality association. Pro-inflammatory diets independently increase all-cause mortality in older adults, partially mediated through eGFR. Dietary interventions and renal monitoring may reduce this risk.